1994
DOI: 10.1523/jneurosci.14-03-01433.1994
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell factor is a neurotrophic factor for neural crest-derived chick sensory neurons

Abstract: We have found that stem cell factor (SCF) selectively enhances the survival of cultured embryonic chick dorsal root ganglia (DRG) neurons. Neurons grown in the presence of SCF expressed both neurofilament 150 kDa subunit and calcitonin-gene related peptide. SCF does not, however, enhance the survival of parasympathetic, placode-derived sensory or sympathetic neurons in culture. Combining SCF with brain-derived neurotrophic factor or neurotrophin-3, but not with NGF, maintains more neurons than either factor al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…From E5 onwards, some cells in the dorsal area of the dorsal root ganglia (DRG) were c-kit positive (not shown). This is in agreement with the in vitro studies of Carnahan et al (1994) who found that the Steel factor has a survival effect on medio-dorsal DRG neurons. The mesenchyme of the branchial arches was also strongly labelled by the c-kit probe.…”
Section: E9supporting
confidence: 93%
“…From E5 onwards, some cells in the dorsal area of the dorsal root ganglia (DRG) were c-kit positive (not shown). This is in agreement with the in vitro studies of Carnahan et al (1994) who found that the Steel factor has a survival effect on medio-dorsal DRG neurons. The mesenchyme of the branchial arches was also strongly labelled by the c-kit probe.…”
Section: E9supporting
confidence: 93%
“…It has been shown that SCF acts as a neurotrophic factor, supporting neuron survival during development of the peripheral nervous system. 28,29 …”
Section: Discussionmentioning
confidence: 99%
“…Application of granulation tissue, rich in ED1 ϩ and ED2 ϩ macrophages, enhances regeneration of peripheral nerves after a test crush lesion (Miyauchi et al, 1997), a responses that may involve IL-1, insofar as IL-1 stimulates the local synthesis of nerve growth factor (NGF) by infiltrating macrophages (Heumann, 1987). Many factors produced by lymphoid cells are neurotrophic, including interleukins other than IL-1 (Kashima et al, 1992;Mehler et al, 1993;Awatsuji et al, 1993;Araujo and Cotman, 1993;van Coelln et al, 1995), granulocyte-macrophage colony-stimulating factor (van Coelln et al, 1995;Kannan et al, 2000), transforming growth factor-␤ (TGF␤; Poulsen et al, 1994), stem cell factor (Carnahan et al, 1994), and leukemia inhibitor factor (Murphy et al1993). Recently, IL-12 and IL-3 also have been reported to stimulate sympathetic neurite growth in mouse sympathetic superior cervical ganglion neurons (Kannan et al, 2000;Lin et al, 2000).…”
Section: Discussionmentioning
confidence: 99%